IV. The Impact of Digital Economy on Innovation Performance Among Belt and Road Countries - Zhao, Yanwen; Zhang, Xin (The Impact of Digital Economy on One Belt One Road Initiative, 2025)
The digital economy has deeply influenced all sectors of national economic development, becoming a critical engine for global economic growth and national innovation performance. Nevertheless, significant gaps persist among developed, developing, and less-developed countries in their levels of digital economic advancement. Given this imbalance, exploring how the digital economy impacts innovation performance in "Belt and Road" countries is essential. This study examines mechanisms through which the digital economy influences innovation performance across these nations. Findings provide valuable insights to enhance competitiveness, support innovation, and address global disparities. The study offers practical recommendations for policymakers in "Belt and Road" countries aiming t.